Propuesta de diseño de sistema anti-spam para sms aplicado a Movistar Perú - Castañeda Chavez, Roberto Augusto (2013)
The Peruvian mobile telecommunications has grown the past 20 years, since the 52 thousand mobile telephones in 1994 where the people only could make some voice calls, later with 4 millions of mobile telephones reach exchanged each other 474 millions of short text messages (SMS) to currently numbers of 28 millions of mobile phones sending and receiving 5.5 billions of SMS each year._x000D_ The growing in our country has been marked by the new economy in the digital era like Mobile Telecommunications and my main goal is send to you all a proposal to secure this market and protect to millions of current users and new potential users of this technologies in coming years._x000D_ My thesis proposal will try avoid the cyber crime through the mobile telephones at Peru. My proposal is based in an AntiSPAM SMS System and has the goal of maintain the right use of this technologies to benefit to millions of people and thousands of business users of Movistar,_x000D_ the largest company of mobile telecommunications in Peru._x000D_ As result of many years of research and hard work in the telecommunications area I would like to offer to you a thesis with a logical definition to avoid the cybercrime such as SPAM and Smishing ( in the context of information security, refers to psychological manipulation of people into performing actions or divulging confidential information)